2014
DOI: 10.3390/molecules19056368
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and Biological Evaluation of Glycyrrhizin Analogs as Anticancer Agents Targeting EGFR

Abstract: Glycyrrhizin (GA) analogs in the form of 3-glucuronides and 18-epimers were synthesized and their anticancer activities were evaluated. Alkaline isomerization of monoglucuronides is reported. In vitro and in vivo studies showed that glycyrrhetinic acid monoglucuronides (GAMGs) displayed higher anticancer activities than those of bisglucuronide GA analogs, while anticancer activity of the 18α-epimer was superior to that of the 18β-epimer. 18α-GAMG was firstly nicely bound to epidermal growth factor receptor (EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Also, the epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein that defines a family of tyrosine kinase receptors (TKRs). Mice manganese lacking EGFR show delayed regeneration after partial hepatectomy (PH), which demonstrates that EGFR is a critical regulator of hepatocyte proliferation during liver regeneration . Hence, EGFR has long been an attractive candidate as an anticancer drug target.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein that defines a family of tyrosine kinase receptors (TKRs). Mice manganese lacking EGFR show delayed regeneration after partial hepatectomy (PH), which demonstrates that EGFR is a critical regulator of hepatocyte proliferation during liver regeneration . Hence, EGFR has long been an attractive candidate as an anticancer drug target.…”
Section: Introductionmentioning
confidence: 99%
“…To develop anticancer agents, much effort has been made to interfere with the activity of the epidermal growth factor receptor (EFGR), a main anticancer drug target (Ye et al., ). For example, 18α‐GAMG is an effective drug for cancer therapy, exhibiting EGFR inhibitory activity that is stronger than the positive control erlotinib (Yang et al., ). In addition, 18α‐GAMG exhibited inhibition of abnormal cell proliferation and is nontoxic to human normal cell lines (Tang et al., ).…”
Section: Characteristics Of Gamgmentioning
confidence: 99%
“…According to molecular docking and biological assay results, 18α‐GAMG possesses higher binding affinity to EGFR and exhibits a stronger inhibition against identical tumor cell lines compared to 18β‐GAMG, explaining its stronger anticancer activity (Yang et al., ). An analysis of the results of computer‐generated molecular docking showed that binding of 18α‐GAMG to EGFR via six hydrogen bonds with ASP831, GLU738, THR766 (three bonds), and LYS721 and one charge interaction formed by the interaction of the end group of LYS692 with a carboxyl (Figure A).…”
Section: Characteristics Of Gamgmentioning
confidence: 99%
See 2 more Smart Citations